Differences in the Effectiveness of Dynamic Stretching Exercise and Static Stretching Exercise on Lumbar Flexibility for Elderly - Nur Safitri, Laila; Wardhani, Riska Risty; Imron, Mohammad Ali (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: Muscle flexibility begins to decline around 20% - 30% at the age of 30-70 years old. Decreased flexibility of the lumbar muscles will result in various problems. The condition will continue to worsen if stretching is not done. The study is to investigate the difference in effectiveness difference of dynamic stretching exercise and static stretching exercise on lumbal flexibilities in the elderly. Methods: The study was experimental with pre and post-test two-group design. The data were taken by using a random sampling technique. The samples were 32 people aged 60 – 79 years old. Results: The result of data analysis using a Paired Sample t-test in groups I and II showed p=0.000 (p<0.05) meaning that there was no significant difference in improving lumbal flexibilities in the elderly. Conclusion: Static and dynamic stretching both enhance flexibility, but static stretching is more effective for flexibility improvement, while dynamic stretching better enhances muscle power and performance quality.